2014
DOI: 10.1111/ssm.12073
|View full text |Cite
|
Sign up to set email alerts
|

The Science Teaching Self‐Efficacy of Prospective Elementary Education Majors Enrolled in Introductory Geology Lab Sections

Abstract: This study examined prospective elementary education majors' science teaching self‐efficacy while they were enrolled in an introductory geology lab course for elementary education majors. The Science Teaching Efficacy Belief Instrument Form B (STEBI‐B) was administered during the first and last lab class sessions. Additionally, students were asked an open‐ended question to describe their experience in the education majors' geology lab. The results of the STEBI‐B were analyzed using paired t‐tests to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
(89 reference statements)
1
1
0
3
Order By: Relevance
“…This may indicate that the previous experiences they had with poetry and science integration were not as in‐depth as the integrative unit taught among the faculty members in this study. This finding corroborates the impact of collaboratively modeling high‐quality integrative poetry and science teaching and learning experiences for PSTs (Baldwin, 2014; Bergeson & Beschorner, 2020; Boice et al, 2021; Fenton & Essler‐Petty, 2019; Hechter, 2011; Vardell & Wong, 2014, 2019). Since the PSTs had not yet participated in an intensive teaching internship and had limited teaching experience, they may have also had low SE about their teaching abilities in general (Cantrell et al, 2003).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This may indicate that the previous experiences they had with poetry and science integration were not as in‐depth as the integrative unit taught among the faculty members in this study. This finding corroborates the impact of collaboratively modeling high‐quality integrative poetry and science teaching and learning experiences for PSTs (Baldwin, 2014; Bergeson & Beschorner, 2020; Boice et al, 2021; Fenton & Essler‐Petty, 2019; Hechter, 2011; Vardell & Wong, 2014, 2019). Since the PSTs had not yet participated in an intensive teaching internship and had limited teaching experience, they may have also had low SE about their teaching abilities in general (Cantrell et al, 2003).…”
Section: Discussionsupporting
confidence: 74%
“…Similarly, additional studies have found that modeling effective science teaching strategies can have a positive effect on PSTs' EO toward teaching science (Settlage, 2000; Yoon et al, 2006), and collaborations among science and teacher education faculty can improve PSTs' SE toward teaching science (Hechter, 2011). More specifically, Baldwin (2014) described how numerous studies over the past two decades have found science teaching methods courses to have a positive influence on elementary PSTs' SE toward teaching science. From an interdisciplinary perspective, Fenton and Essler‐Petty (2019) found that a combined elementary math and science teaching methods course (co‐taught by math and science education faculty members) resulted in increased SE, EO, and confidence to teach STEM lessons among elementary PSTs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Baldwin (2014) sınıf öğretmenliği öğretmen adaylarının fen edebiyat fakültesinden almak durumunda oldukları yer bilimi laboratuvar dersinin bilimsel içeriğine ek olarak ilköğretim seviyesinde uygulanabilecek etkinliklerle zenginleştirildiğinde ve ders içeriği gelecek mesleki yaşantılarıyla ilişkilendirilerek yürütüldüğünde öğretmen adaylarının fen öğretimi öz yeterlik inançlarında iyileşme olduğunu fakat sonuç beklentisinde aynı etkinin olmadığını ortaya koymuştur. Benzer şekilde, Posnanski (2007) yaptığı çalışmada yapılandırmacı etkinlikler çerçevesinde, bilimin doğası, fen standartları ve ilköğretim seviyesinde uygulamalarla zenginleştirilerek verilen yer bilimi dersini alan sınıf öğretmenliği öğretmen adaylarının fen öğretimi öz-yeterlik inançlarında yükselme olduğunu bulmuştur.…”
Section: Fen öğRetimi öZ-yeterlik đNancıunclassified
“…Nitekim fen alan derslerinin öğretim şeklini değiştirerek, yöntem derslerinde olduğu gibi yeni yaklaşımlara uygun pedagojik uygulamalarla bütünleştirilerek öğretmen adaylarının eğitimlerinin erken dönemlerinden başlayarak bilimi öğretecekleri şekilde öğrenmeleri öğretmen adaylarının özellikle fen öğretimi öz-yeterlik inançlarını güçlendirdiği görülmektedir (Baldwin, 2014;Posnanski, 2007). Baldwin (2014) sınıf öğretmenliği öğretmen adaylarının fen edebiyat fakültesinden almak durumunda oldukları yer bilimi laboratuvar dersinin bilimsel içeriğine ek olarak ilköğretim seviyesinde uygulanabilecek etkinliklerle zenginleştirildiğinde ve ders içeriği gelecek mesleki yaşantılarıyla ilişkilendirilerek yürütüldüğünde öğretmen adaylarının fen öğretimi öz yeterlik inançlarında iyileşme olduğunu fakat sonuç beklentisinde aynı etkinin olmadığını ortaya koymuştur. Benzer şekilde, Posnanski (2007) yaptığı çalışmada yapılandırmacı etkinlikler çerçevesinde, bilimin doğası, fen standartları ve ilköğretim seviyesinde uygulamalarla zenginleştirilerek verilen yer bilimi dersini alan sınıf öğretmenliği öğretmen adaylarının fen öğretimi öz-yeterlik inançlarında yükselme olduğunu bulmuştur.…”
Section: Fen öğRetimi öZ-yeterlik đNancıunclassified
See 1 more Smart Citation